INDUKSI KEJUTAN SUHU 360 C TERHADAP PERKEMBANGAN EMBRIO DAN KEBERHASILAN POLIPLOIDISASI KATAK (Rana cancrivora) (Jurnal Pelangi : Research of Education and Development, 2014)
Polyploidy in the frog Rana cancrivora can be done by providing a temperature shock. The thing need to consider in treatment temperature shock at  the egg is the beginning of a shock, temperature of shock and duration of shock. The research aims to identify and test the effect of temperature shock 36⁰C to the development of the embryo, and the success of poliploidisation of frog R. Cancrivora. The research was conducted in Biology Laboratory STKIP PGRI West Sumatra. The results shows that administration of 36⁰C temperature shock on egg fertilization influences on the development of frog embryos R. Cancrivora i.e. on the treatment D (45 minutes after fertilization). Yet, the temperature shock is 36⁰C does not show any influence on the success of poliploidisation of frog R. Cancrivora.